Zakat Compliance among Citrus Farmers: Legal Awareness in Nagari Koto Tangah, West Pasaman Regency - Elnita Elnita; Duhriah Duhriah; Fauzi Yati (Saqifah: Jurnal Hukum Ekonomi Syariah, 2025)
The legal awareness of the community in paying zakat, especially on citrus agricultural products, is an important aspect in supporting social welfare and economic justice. The purpose of this study is to analyze the level of legal awareness of the community in paying zakat on oranges. The study uses a qualitative approach. Primary data was obtained through interviews and secondary data was obtained from journals, books, research results and a number of literature or academic studies. The results of this study are that the background of farmers not paying zakat on oranges is. First, the community considers that zakat on oranges cannot be paid because of the large number of expenses for their living needs and the zakat that is usually paid is zakat on rice, while no community pays zakat on oranges so they are also reluctant to pay zakat on oranges because of the community's habits. Second, the legal awareness of orange farmers in Nagari Persiapan Koto Tangah is relatively low due to the lack of knowledge and understanding of the law which has an impact on the behavior of orange farmers, namely the zakat that is paid, but not in accordance with the provisions.